Multinational dietary changes and anxiety during the coronavirus pandemic-findings from Israel - Vered Kaufman-Shriqui; Daniela Abigail Navarro; Olga Raz; Mona Boaz (BMC, 2021)
Abstract Background Increased anxiety was frequently reported during the 2020 global COVID-19 pandemic. An association between anxiety and increased body weight has been documented. Identifying associations between diet quality and anxiety may facilitate the development of preventive dietary policy, particularly relevant since obesity appears to increase the risk of adverse COVID-19 outcomes. In this study we aim to examine associations between changes in diet pattern and body weight and anxiety levels during the COVID-19 pandemic among Israeli respondents to an international online survey. Methods Conducted between March 30-April 252,020, this was cross-sectional, international and online study. The questionnaire was developed and tested in Hebrew and translated into six other languages: English, Arabic, Spanish, French, Italian, and Russian. The survey was conducted on a Google Survey platform, the link to which was posted on several social media platforms. Adults aged 18 or older who saw and responded to the link on a social media site comprised the study population. Results Of the 3979 eligible respondents, 1895 indicated their current location as Israel. Most Israeli respondents completed the survey in Hebrew (83.2%) followed by Arabic (9.4%), though responses were recorded in all seven of the survey languages. The median age was 33 (IQ = 22) years, and 75.7% were female. Almost 60% indicated that their pre-pandemic diet was healthier than their current diet, and 25.2% indicated they had gained weight during the pandemic. The median Mediterranean diet score was 9 (IQ = 3). While the median General Anxiety Disorder (GAD-7) score was 5 (IQ = 8), only 37.3% of participants reported at least mild anxiety (a GAD-7 score of 5 or more), while 10.7% reported moderate anxiety or greater (a GAD-7 score of 10 or more). In a multivariate logistic regression model of at least mild anxiety, being male and completing the survey in Hebrew significantly reduced odds of at least mild anxiety, while a worsening of diet quality during the pandemic, weight gain, and isolation significantly increased odds of at least mild anxiety. Conclusions During the COVID pandemic, changes in nutrition quality and habits were associated with greater anxiety. These findings suggest the need for routine and continuous surveillance of the nutritional and psychological consequences of outbreaks as part of healthcare preparedness efforts. Organizations responsible for community-based health services (such as Israeli health plans) should adopt specific interventions to improve case finding and support individuals at increased risk of anxiety and declining nutrition status within primary healthcare settings. These interventions should include the provision of appropriate diagnostic instruments, training of medical staff, feedback to physicians and nurses, and raising awareness among the relevant patient population and their caregivers. Primary care physicians should refer people with high anxiety or substantial weight gain during the pandemic to appropriate mental health and dietetic treatment, as needed. Trial registration NCT04353934 .